2006
DOI: 10.1074/jbc.m513212200
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Identification and Characterization of a Family of Kinases with Homology to Ca2+/Calmodulin-dependent Protein Kinases I/IV

Abstract: Despite the critical importance of Ca 2؉ /calmodulin (CaM)-dependent protein kinase (CaMK) II signaling in neuroplasticity, only a limited amount of work has so far been available regarding the presence and significance of another predominant CaMK subfamily, the CaMKI/CaMKIV family, in the central nervous system. We here searched for kinases with a core catalytic structure similar to CaMKI and CaMKIV. We isolated full-length cDNAs encoding three mouse CaMKI/CaMKIV-related kinases, CLICK-I (CL1)/doublecortin an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 67 publications
0
33
0
Order By: Relevance
“…Our observation of a frequent mutant allele LOH in the region telomeric to MLH1, in particular, implicated this region as a possible location of additional targets for LOH irrespective of MLH1. Potential target genes include DCAMKL3 (KIAA1765), which has doublecortin and CaM-kinase-like 3 motifs and may function in cell signaling (Nagase et al, 2000;Ohmae et al, 2006), and STAC (SRC homology 3 and cysteine-rich domain), which may play a role in cell proliferation, transformation and apoptosis (Suzuki et al, 1996;Satoh et al, 2006). The region at 3p21-22 is often deleted in human epithelial malignancies (Protopopov et al, 2003), and future studies should examine if DCAMKL3 or STAC, or other genes from this region, are directly involved in these tumorigenic processes.…”
Section: Discussionmentioning
confidence: 99%
“…Our observation of a frequent mutant allele LOH in the region telomeric to MLH1, in particular, implicated this region as a possible location of additional targets for LOH irrespective of MLH1. Potential target genes include DCAMKL3 (KIAA1765), which has doublecortin and CaM-kinase-like 3 motifs and may function in cell signaling (Nagase et al, 2000;Ohmae et al, 2006), and STAC (SRC homology 3 and cysteine-rich domain), which may play a role in cell proliferation, transformation and apoptosis (Suzuki et al, 1996;Satoh et al, 2006). The region at 3p21-22 is often deleted in human epithelial malignancies (Protopopov et al, 2003), and future studies should examine if DCAMKL3 or STAC, or other genes from this region, are directly involved in these tumorigenic processes.…”
Section: Discussionmentioning
confidence: 99%
“…Validation of microarray signals by qPCR against specific DCAMKL1 splice variants (data not shown) showed that the NGF-regulated transcript is doublecortin-like kinase (DCLK)-short (Silverman et al 1998;Hevroni et al 1998;Engels et al 2004). DCLK-short has been shown to repress CREB-mediated transcription (Silverman et al 1999;Ohmae et al 2006), possibly complexed in a signaling endosome (Schenk et al 2007). As CREB is an important transcription factor in NGF-induced effects (Finkbeiner et al 1997) it would be of interest to investigate whether increasing up-regulation of DCLK-short represents an increasing negative feedback mechanism on NGF stimulated CREB activation.…”
Section: Intracellular Signaling Cascadementioning
confidence: 99%
“…After mounting, 24-bit color images were acquired by scanning of the sections. Digoxigenin signals were isolated by uniformly subtracting the counterstaining color component using Photoshop version 9.0.2 (Adobe Systems) (Ohmae et al, 2006;TakemotoKimura et al, 2007).…”
Section: Ar2 Mice Intercrosses Of Adar2mentioning
confidence: 99%